Implementasi Program Islamic Character Building (ICB) Dalam Membentuk Karakter Islami Siswa di SMPIT Nurul Azmi Medan - Alfi Zan Nur; Nadlrah Naimi (Universitas Labuhanbatu, 2023)
This study aims to determine the implementation of the Islamic Character Building (ICB) program in shaping the Islamic character of students at SMPIT Nurul Azmi Medan. The objectives of this Islamic Character Building Program are: 1) To describe the Implementation of the Islamic Character Building Program at SMPIT Nurul Azmi Medan. 2) To describe the purpose of the Islamic Character Building Program at SMPIT Nurul Azmi Medan. 3) To analyze what factors support and hinder the Islamic Character Building Program at SMPIT Nurul Azmi Medan. This research uses a qualitative approach with a descriptive research type. The data collection methods used are observation, interview, and documentation methods. The results showed that the ICB Program at SMPIT Nurul azmi Medan is an effective program to be implemented in shaping and building students' Islamic character. Supporting factors in this program are the readiness of the material that has been designed, the availability of infrastructure, the cooperation between the principal, teachers and parents, and the active role of students in participating in program activities. The inhibiting factor is the lack of socialization to new educators about the use of applications that support the Islamic Character Building (ICB) Program and the limited time for the supervising teacher to deliver the existing material.